2013
DOI: 10.1097/opx.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative Responses Under Different Stimulus Conditions

Abstract: The results suggest that the accommodative response in the steady state may be affected by the method used for inducing AS and the sequence of AS presented. The AEA is suggested to be used in the evaluation of the accuracy of the ASRC in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Repetition of the statistical tests with slopes and accommodative error indices derived over stimulus intervals 1.00 to 4.00 D and 1.00 to 5.00 D rather than the linear range led to broadly similar conclusions, as also did the use of the simpler accommodative error area (AEA) instead of the accommodative error index …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Repetition of the statistical tests with slopes and accommodative error indices derived over stimulus intervals 1.00 to 4.00 D and 1.00 to 5.00 D rather than the linear range led to broadly similar conclusions, as also did the use of the simpler accommodative error area (AEA) instead of the accommodative error index …”
Section: Resultsmentioning
confidence: 75%
“…The difference between these does not differ significantly from zero (mean difference 0.05 D, 95 per cent confidence limits ‐0.02 and 0.11 D); however, it is consistent with the findings of Yeo, Kang and Tang, even though the tasks, methods used to control the stimulus vergence and other factors differed between the two studies. For example, some studies have found that the way that stimulus vergence is varied affects the accommodative response, as also does binocular compared to monocular viewing (Table ). Yeo, Kang and Tang's young Chinese subjects viewed the texts directly at different distances, whereas in the present case, involving adults, stimulus vergence was varied with lenses.…”
Section: Discussionmentioning
confidence: 99%
“…The ASRC obtained using each method was fitted with a third‐degree polynomial equation . Figure shows an example for a single subject.…”
Section: Methodsmentioning
confidence: 99%
“…The accommodative stimulus–response curve (ASRC) describes the accommodative response as a function of the accommodative stimulus. This curve can be used to derive important parameters of accommodation, such as the slope of the accommodative response, the accommodative error index, which is calculated from the area between the regression line for the linear part of the accommodative curve and the 1:1 line divided by the correlation coefficient and the accommodative error area, which is the area between the accommodative curve including the non‐linear region and the 1:1 line. These parameters also provide insight into potential relationships between accommodation and ocular anomalies, such as amblyopia and myopia …”
mentioning
confidence: 99%
See 1 more Smart Citation